Preventive and therapeutic efficacy of finasteride and dutasteride in TRAMP mice - Opoku-Acheampong, Alexander B.; Unis, Dave; Henningson, Jamie N.; Beck, Amanda P.; Lindshield, Brian L. (My University, 2013)
Background: The prostate cancer prevention trial (PCPT) and Reduction by dutasteride of Prostate Cancer Events (REDUCE) trial found that 5α-reductase (5αR) inhibitors finasteride and dutasteride respectively, decreased prostate cancer prevalence but also increased the incidence of high-grade tumors. 5αR2 is the main isoenzyme in normal prostate tissue; however, most prostate tumors have high 5αR1 and low 5αR2 expression. Because finasteride inhibits only 5αR2, we hypothesized that it would not be as efficacious in preventing prostate cancer development and/or progression in C57BL/6 TRAMP x FVB mice as dutasteride, which inhibits both 5αR1 and 5αR2. Method/Principal Findings: Six-week-old C57BL/6 TRAMP x FVB male mice were randomized to AIN93G control or pre- and post- finasteride and dutasteride diet (83.3 mg drug/kg diet) groups (n =30–33) that began at 6 and 12 weeks of age, respectively, and were terminated at 20 weeks of age. The pre- and post- finasteride and dutasteride groups were designed to test the preventive and therapeutic efficacy of the drugs, respectively. Final body weights, genitourinary tract weights, and genitourinary tract weights as percentage of body weights were significantly decreased in the Pre- and Post-dutasteride groups compared with the control. The Post-dutasteride group showed the greatest inhibition of prostatic intraepithelial neoplasia progression and prostate cancer development. Surprisingly, the Post-dutasteride group showed improved outcomes compared with the Pre-dutasteride group, which had increased incidence of high-grade carcinoma as the most common and most severe lesions in a majority of prostate lobes. Consistent with our hypothesis, we found little benefit from the finasteride diets, and they increased the incidence of high-grade carcinoma. Conclusion: Our findings have commonalities with previously reported PCPT, REDUCE, and the Reduction by dutasteride of Clinical Progression Events in Expectant Management (REDEEM) trial results. Our results may support the therapeutic use of dutasteride, but not finasteride, for therapeutic or preventive use.
Keywords: Prostate cancer prevention; Dutasteride; Finasteride